Pre-transplant HLA Antibodies and Delayed Graft Function in the Current Era of Kidney Transplantation - Morath, Christian; Döhler, Bernd; Kälble, Florian; Pego da Silva, Luiza; Echterdiek, Fabian; Schwenger, Vedat; Živčić-Ćosić, Stela; Katalinić, Nataša; Kuypers, Dirk; Benöhr, Peter; Haubitz, Marion; Ziemann, Malte; et al. (Frontiers in Immunology, 2020)
Delayed graft function (DGF) occurs in a significant proportion of deceased donor kidney transplant recipients and was associated with graft injury and inferior clinical outcome. The aim of the present multi-center study was to identify the immunological and non-immunological predictors of DGF and to determine its influence on outcome in the presence and absence of human leukocyte antigen (HLA) antibodies. 1,724 patients who received a deceased donor kidney transplant during 2008–2017 and on whom a pre-transplant serum sample was available were studied. Graft survival during the first 3 post-transplant years was analyzed by multivariable Cox regression. Pre-transplant predictors of DGF and influence of DGF and pre-transplant HLA antibodies on biopsy-proven rejections in the first 3 post-transplant months were determined by multivariable logistic regression. Donor age ≥50 years, simultaneous pre-transplant presence of HLA class I and II antibodies, diabetes mellitus as cause of end-stage renal disease, cold ischemia time ≥18 hours, and time on dialysis >5 years were associated with increased risk of DGF, while the risk was reduced if gender of donor or recipient was female or the reason for death of donor was trauma. DGF alone doubled the risk for graft loss, more due to impaired death-censored graft than patient survival. In DGF patients, the risk of death-censored graft loss increased further if HLA antibodies (hazard ratio HR=4.75, P<0.001) or donor-specific HLA antibodies (DSA, HR=7.39, P<0.001) were present pre-transplant. In the presence of HLA antibodies or DSA, the incidence of biopsy-proven rejections, including antibody-mediated rejections, increased significantly in patients with as well as without DGF. Recipients without DGF and without biopsy-proven rejections during the first 3 months had the highest fraction of patients with good kidney function at year 1, whereas patients with both DGF and rejection showed the lowest rate of good kidney function, especially when organs from ≥65-year-old donors were used. In this new era of transplantation, besides non-immunological factors, also the pre-transplant presence of HLA class I and II antibodies increase the risk of DGF. Measures to prevent the strong negative impact of DGF on outcome are necessary, especially during organ allocation for pre-sensitized patients.